The Need For A MUI Fatwa On People With Disabilities - Rizani, Akhmad Kamil; Kharlie, Ahmad Tholabi; Maggalatung, A Salman; Pelu, Ibnu Elmi Acmad Slamat; Dakhoir, Ahmad; Darojat, Much Hasan (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This article explores the need for an MUI fatwa on persons with disabilities. Humans are creatures of God who are created to have a set of rights as humans that must be safeguarded and protected. Islam recognizes and respects the existence of people with disabilities and upholds their rights. This is because Islam encourages its followers to have compassion and love for all humanity. The method used in this research is qualitative research with a literature study research type. The literature research approach involves collecting and analyzing data from various literature related to the need for an MUI fatwa on persons with disabilities. The result of this research shows that the need for an MUI fatwa on persons with disabilities serves as an effort to increase the awareness of all Indonesian people, especially Muslims, about the importance of showing respect and value to persons with disabilities as humanitarian brothers, national brothers and even Islamic brothers. It can also be used to strengthen the rights of persons with disabilities in various fields and encourage the creation of an inclusive environment.